UPAYA PASRAMAN PADMA BHUANA SARASWATI DALAM MEWUJUDKAN SISYA YANG CERDAS BERBUDAYA - I Nyoman Santiawan; I Nyoman Warta (Bawi Ayah: Jurnal Pendidikan Agama dan Budaya Hindu, 2020)
Pasraman Padma Bhuana Saraswati is a parsaman located in the city of Yogyakarta that has a vision to form a cultured Smart Sisya. This study aims to find out how pasraman efforts Padma Bhuana Saraswati in realizing the vision of the institution. This study uses a qualitative approach, so that data collection is done by observation and direct interviews with selected respondents. The results of this study reveal the success of Pasraman Padma Bhuana Saraswati in forming intelligent cultured students, namely: 1. The role of parents, 2. The role of teachers, and 3. The role of managers of pasraman. Of these three factors, the role of parents has a very high influence on the success of postgraduate education in Padma Bhuana Saraswati. Parents have an important role that is directing, reminding and accompanying students during the learning process so that parents often become educators in Pasraman. With these 3 factors, Pasraman Padma Bhuana Saraswati was able to achieve a shared vision and goals. Not only that, until now Pasraman Padma Bhuana Saraswati is very active in community religious and social activities such as Social Service and involvement in national-scale cultural performances